2005
DOI: 10.1086/502534
|View full text |Cite
|
Sign up to set email alerts
|

Failure to Control an Outbreak of Multidrug-ResistantStreptococcus pneumoniaein a Long-Term–Care Facility Emergence and Ongoing Transmission of a Fluoroquinolone-Resistant Strain

Abstract: Objectives:To characterize risk factors associated with pneumococcal disease and asymptomatic colonization during an outbreak of multidrug-resistantStreptococcus pneumoniae(MDRSP) among AIDS patients in a long-term–care facility (LTCF), evaluate the efficacy of antimicrobial prophylaxis in eliminating MDRSP colonization, and describe the emergence of fluoroquinolone resistance in the MDRSP outbreak strain.Design:Epidemiologic investigation based on chart review and characterization of SP strains by antimicrobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…This trend appears to have subsequently declined to one outbreak per year. Of the 42 outbreaks reported, 24 occurred in the USA, 10,11,13,14,25,26,38,39,42,44 10 in the UK, 9,12,15,17,20,21,24,33,36 three in Canada, 30 two in France 28,35 and one each in Israel, 34 the Netherlands 32 and Spain. 27 The majority of outbreaks 14 occurred in hospital settings 12,13,15,20e22,31e34,36,43,45 followed by long term care facilities (LTCF) in which 12 were reported.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This trend appears to have subsequently declined to one outbreak per year. Of the 42 outbreaks reported, 24 occurred in the USA, 10,11,13,14,25,26,38,39,42,44 10 in the UK, 9,12,15,17,20,21,24,33,36 three in Canada, 30 two in France 28,35 and one each in Israel, 34 the Netherlands 32 and Spain. 27 The majority of outbreaks 14 occurred in hospital settings 12,13,15,20e22,31e34,36,43,45 followed by long term care facilities (LTCF) in which 12 were reported.…”
Section: Resultsmentioning
confidence: 99%
“…25,38,44,47 Carter et al, reported an outbreak of 10 cases with serotype information available for seven; five with serotype 23F and two with serotype 2. 14 We could calculate an attack rate in 11 of the outbreaks; median: 11.7 (range 7.4e14.9), and a case fatality ratio for all the outbreaks, median: 24% (range 0e44).…”
Section: Outbreaks Of Serious Pneumococcal Disease In Hospitalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Age, previous hospitalization, and previous antimicrobial therapy have been thought to contribute to penicillin-resistant pneumococcal infection in nosocomial outbreaks (18,27). Previous studies conducted to determine the antimicrobial susceptibilities of isolates from NPI found that a high percentage of pneumococcal pathogens had multidrug resistance, including resistance to new quinolones (4,5,28,39). Masaki et al reported a possible relationship between the pulsed-field gel electrophoresis (PFGE) patterns of Moraxella catarrhalis isolates from hospital-and community-acquired respiratory infections in a community hospital (20).…”
mentioning
confidence: 99%